Inflammatory Cytokine Profile in Crohn's Disease Nonresponders to Optimal Antitumor Necrosis Factor Therapy. Issue 3 (March 2019) - Yarur, Andres J.; Jain, Anjali; Quintero, Maria A.; Czul, Frank; Deshpande, Amar R.; Kerman, David H.; Abreu, Maria T.
Abstract : Background: A significant number of patients receiving therapy with antitumor necrosis factor (TNF) agents for Crohn's disease experience primary or secondary nonresponse. The aim of this study was to assess whether patients with nonresponse to anti-TNF agents have increased expression of alternative cytokine pathways. Methods: We designed a prospective, cross-sectional study that included patients with Crohn's disease receiving anti-TNF undergoing colonoscopy with adequate serum trough drug levels (≥8 µg/mL) and without anti-drug antibodies. Inflammatory cytokines and cell adhesions markers measured included intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1, interleukin (IL)-8, IL-1β, and IL-6. The primary outcome was the presence of active endoscopic inflammation defined as the presence of at least 1 ulceration ≥5 mm. Results: In total, 47 patients were included. Patients with active inflammation had significantly higher levels of ICAM-1 and IL-1β when compared with those without intestinal inflammation (45.9 vs. 35.8 ng/mL, P <0.0001 and 3.2 vs. 1.5 pg/mL, P =0.002, respectively). There were no significant differences in the other study variables. Using receiving operating curves, ICAM and IL-1β had a good correlation (receiver operating characteristic ≥0.8) with inflammation in this cohort of patients with "anti-TNF resistance." The results were similar in the group of patients with previous anti-TNF exposure. Conclusion: Our study suggests that patients who have active inflammation with seemingly adequate serum anti-TNF levels have increased levels of specific inflammatory pathways that may serve as biomarkers of nonresponse as well as potential targets of therapy in anti-TNF nonresponders.